Correlation of hypoxic signalling to histological grade and outcome in cartilage tumours - Boeuf, Stephane; Bovée, Judith Veronica Maria Geeske; Lehner, Burkhard; Hogendoorn, Pancras C. W.; Richter, Wiltrud (Histopathology, 2010)
Boeuf S, Bovée J V M G, Lehner B, Hogendoorn P C W & Richter W (2010) Histopathology56, 641-651 Correlation of hypoxic signalling to histological grade and outcome in cartilage tumours Aims: The molecular mechanisms underlying the progression of central chondrosarcoma are so far poorly understood. The aim of this study was to identify genes involved in the progression of these tumours by comparison of gene expression and correlation of expression profiles to histological grade and clinical outcome. Methods and results: Array-based gene expression profiling of 19 chondrosarcoma samples was performed. Beside differences in the expression of cartilage matrix molecules, high-grade chondrosarcoma showed enhanced expression of the matrix metalloproteinase MMP-2 and of the hypoxia-inducible molecule galectin 1. Immunohistochemical analysis of galectin 1 and of further hypoxia-associated proteins was performed on 68 central and peripheral tumour samples. Hypoxia-inducible factor 1α (HIF-1α) activation was significantly elevated in high-grade central chondrosarcoma. A negative correlation of carbonic anhydrase IX expression to metastasis-free survival was independent of histological grade. Conclusions: The expression patterns identified in this study point towards a substantial role for angiogenic and hypoxic signalling in chondrosarcoma progression. The constitutive activation of the transcription factor HIF-1α in high-grade chondrosarcoma could play a central role in the regulation of cell metabolism and vascularization in these tumours and may, for this reason, represent a potential target for chondrosarcoma therapy.
Gesehen am 01.02.2023